A Review of Novel Antioxidant Ergothioneine: Biosynthesis Pathways, Production, Function and Food Applications - Haijing Zhang; Zheng Liu; Zhong Wang; Ziteng Lei; Yan Jia; Wei Chen; Ruoyu Shi; Chengtao Wang (Foods)
Ergothioneine (EGT), a natural thiol compound with potent antioxidant properties, exhibits diverse biological functions, including anti-inflammatory, neuroprotective, and cardioprotective effects. Despite its promising health and food applications, current production methods, such as mushroom-based liquid fermentation, are hindered by low yields and complex processes. Advances in biosynthetic fermentation, including heterologous expression of key pathway genes and optimization of cultivation conditions, offer promising solutions to these challenges. Recent discoveries, such as the catalytic efficiency of mononuclear non-heme iron enzymes like Egt1 and EgtB, have streamlined EGT biosynthetic pathways, reducing steps and increasing yield. The compound’s active transport via the OCTN1 protein facilitates its distribution across tissues, enhancing its therapeutic efficacy and potential in functional foods. Currently employed as an antioxidant and antimelanogenic agent in aquatic products, EGT holds vast potential for broader applications in food systems. This review explores the advancements in EGT production and biosynthesis while emphasizing its prospects as a safe, versatile, and effective natural ingredient for health and industrial applications.